Geopolitik, naturlige grænser og „kartopolitik“ i Arktis - Strandsbjerg, Jeppe (Politik, 2011)
Drawing on insights from Critical Geopolitics and the science studies of Bruno Latour, this article argues that geopolitics in the Arctic today is not only a question of interstate competition but also a struggle about how to define space. If we challenge the notion of geography as being something given or natural, geographical space itself becomes a contested phenomenon. With such a perspective, it appears that there is a more profound geopolitical struggle taking place between indigenous people, represented in this article by the Inuit Circumpolar Council, and states, than there is between states. I introduce the term ‘cartopolitics’ to describe the way in which cartography and measurement establish a particular spatial reality that is necessary for international law to function in relation to sovereignty claims made by Arctic states. In contrast to this scientific rationality of space, the Inuit have laid claim to a different spatiality characterized by shared use and movement across ice. By implication we must recognise this contest over spatiality as a geopolitical struggle that is as important for life in the Arctic as the one that takes place between states only.